Comparison of selected levels of serum elements / minerals in obese dogs - Cihan, H; Ateş , F; Karış, D; Tunca, M; Bozkurt, NC; Parkan Yaramış, Ç; Bilgiç, B; Or, ME (Journal of the Hellenic Veterinary Medical Society, 2023)
Obesity is the most common metabolic disorder defined as excessive adipose tissue accumulation in the body. Elements and minerals are crucial for biological metabolism. There have been limited studies based on the relationship between elements/minerals and obesity in dogs. The study was aimed to evaluate possible alterations of selected serum elements/minerals -copper (Cu), iron (Fe), zinc (Zn), selenium (Se), chromium (Cr), nickel (Ni), calcium (Ca), phosphorus (P), magnesium (Mg), boron (B), cobalt (Co) and aluminum (Al)- in obese dogs. The study groups were categorized as obese group (n:20) and controls (n:10) with different breeds and genders due to body condition scoring system cared under similar conditions fed with dry commercial food once daily. Serum elements/minerals in serum were analyzed by using inductively coupled plasma-optical emission spectrophotometer (ICP-OES). Obese dogs had statistically higher serum Fe levels compared with healthy controls. A positive correlation was found between serum levels of Cr-Ni; Cu-Mg; Cu-Se; Mg-Se; Mg-Ca; Mg-P; B-Co; B-Ca; Ni-Co; Co-Ca and Ca-P in obese dogs. It has been accepted that obesity is a pro-inflammatory process priorly initiating in adipose tissue. Higher serum Fe levels in obese dogs might be related with inflammation during the obesity process. Moreover, the strong correlations among other discussed elements/minerals even with no statistical alterations of serum levels in obese dogs should be elucidated with further studies. Elements and minerals might be evaluated as biomarkers for the determination of effects of obesity in dogs.